KEMAMPUAN PEMECAHAN MASALAH PADA SOAL MATEMATIKA DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Rewi Konitah; Benny Hendriana (JOEL: Journal of Educational and Language Research, 2022)
This Study This study aims to describe the problem-solving abilities of class X SMA students in solving SPLTV math problems in terms of reflective and impulsive cognitive styles. Data collection techniques used are tests, interviews, analysis and drawing conclusions. Based on the results of the data obtained and processed by researchers, it can be seen that from the number of students or students as many as 21 people have different results. For example, it can be seen from the total time in which the fastest count is 138 seconds and 1,078 seconds late, and followed by the average time in seconds, which is 10.61 seconds fastest and 82.92 seconds late, with an error frequency of 10.61 seconds. the lowest is 0 and the highest is 9, with 2 existing categories namely reflective and impulsive.